Topical Applications of Quercetin Improves Wound Repair and Regeneration in Diabetic Rats (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Purpose: There is an urgent need of effective drug/formulation to speed up the healing process in diabetic wounds. In our earlier studies, quercetin has accelerated the healing of nondiabetic wounds. So, we investigated the wound-healing potentials of quercetin in diabetic rats. Materials and methods: A square-shaped cutaneous wound (400mm2) was created on the back of nondiabetic and diabetic rats. They were divided into three groups, viz. healthy control (nondiabetic), diabetic control and diabetic-treated group. Ointment base was topically applied for 21days in healthy and diabetic control groups. Quercetin (0.3%) ointment was similarly applied in third group. Effects of quercetin on repair and regenerations of diabetic wounds in terms of wound closure, inflammation, angiogenesis, fibroblast proliferation, collagen synthesis, epithelialization, axonal regeneration etc was studied. Results: Quercetin accelerated the wound closure and increased the expressions of IL-10, VEGF and TGF-b1 in granulation/healing tissue of diabetic wound. However, quercetin decreased the expression of TNF-a, IL-1b, and MMP-9. Histopathological evaluation revealed amelioration of persistence of inflammatory cells by quercetin in diabetic wounds. There was good quality of granulation tissue, marked fibroblast proliferation, well organized collagen deposition, early regeneration of epithelial layer etc. in the quercetin treated diabetic wounds in comparison to diabetic control group. Results of immunohistochemistry showed more angiogenesis, faster phenotypic switching of fibroblast to myofibroblasts and increased GAP-43 positive nerve fibres in quercetin-treated diabetic wounds. Conclusion: Quercetin ointment at 0.3% w/w concentration modulates cytokines, growth factors and protease, thereby improved repair and regenerations of cutaneous diabetic wounds in rats.
Keywords: Quercetin; diabetic rat; wound healing; cytokines; growth factors; granulation tissue